2021
DOI: 10.1111/bph.15661
|View full text |Cite
|
Sign up to set email alerts
|

Cannabigerolic acid, a major biosynthetic precursor molecule in cannabis, exhibits divergent effects on seizures in mouse models of epilepsy

Abstract: Background and Purpose: Cannabis has been used to treat epilepsy for millennia, with such use validated by regulatory approval of cannabidiol (CBD) for Dravet syndrome. Unregulated artisanal cannabis-based products used to treat children with intractable epilepsies often contain relatively low doses of CBD but are enriched in other phytocannabinoids. This raises the possibility that other cannabis constituents might have anticonvulsant properties.Experimental Approach: We used the Scn1a +/À mouse model of Drav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 84 publications
4
31
0
Order By: Relevance
“…products to treat epilepsy, this study by Anderson and colleagues provides timely further information on the anti-seizure potential of some major cannabinoids often found in high concentrations in these products (Anderson et al, 2021).…”
mentioning
confidence: 93%
“…products to treat epilepsy, this study by Anderson and colleagues provides timely further information on the anti-seizure potential of some major cannabinoids often found in high concentrations in these products (Anderson et al, 2021).…”
mentioning
confidence: 93%
“…While CBD, THC and their precursors, cannabidiolic acid (CBDA) and tetrahydrocannabinolic acid (THCA-A), respectively, are the major cannabinoids present in most cultivars, the minor cannabinoids have also been shown to have pharmacological benefits for various medical conditions [ 4 , 5 ]. Cannabinol (CBN), cannabigerol (CBG) and cannabichromene (CBC) have been shown to exhibit anti-inflammatory properties for various medical conditions, including irritable bowel syndrome [ 6 , 7 , 8 , 9 , 10 ]. There is also evidence to suggest that cannabigerolic acid (CBGA) and cannabidivarin (CBDV) have anti-convulsant properties and they may be useful in the treatment of epilepsy in conjunction with CBD [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cannabinol (CBN), cannabigerol (CBG) and cannabichromene (CBC) have been shown to exhibit anti-inflammatory properties for various medical conditions, including irritable bowel syndrome [ 6 , 7 , 8 , 9 , 10 ]. There is also evidence to suggest that cannabigerolic acid (CBGA) and cannabidivarin (CBDV) have anti-convulsant properties and they may be useful in the treatment of epilepsy in conjunction with CBD [ 10 , 11 ]. Additionally, preliminary animal studies have shown that tetrahydrocannabivarin (THCV) may be useful in delaying the onset of neurodegenerative disorders, such as Parkinson’s disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the beneficial effects of the Cannabis sativa L. plant in the treatment of seizures have been known since ancient times. The active ingredients of this plant are mainly ∆ 9 -tetrahydrocannabinol (∆ 9 -THC) and cannabidiol (CBD), the latter considered much safer and more effective in treating seizures, because it is devoid of the adverse psychotropic effects which represent the main limitation of ∆ 9 -THC. Although the therapeutic potential of CBD in seizure disorders has been known for many years, it is only in the last decade that major progress has been made in characterizing its preclinical and clinical properties as a new ASM [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent study, cannabigerolic acid (CBGA), which is the biosynthetic precursor of all cannabinoids, was found to be more potent than CBD in reducing seizures triggered by a febrile event in a mouse model of Dravet syndrome [9]. Higher doses of CBGA also had pro-convulsant effects on other seizure types, highlighting a limitation of this cannabis constituent in comparison with CBD [9].…”
Section: Introductionmentioning
confidence: 99%